Impact of DSA and immunosuppression minimization on rejection, graft, and patient survival after simultaneous liver–kidney transplantation - Dekeyser, Manon; Taupin, Jean-Luc; Elias, Michelle; Ichaï, Philippe; Herr, Florence; Boudon, Marc; Brunel, Melanie; Sa cunha, Antonio; Coilly, Audrey; Saliba, Faouzi; Durrbach, Antoine (Frontiers in Medicine, 2022)
Background Acute rejection rate is low after simultaneous liver–kidney transplantation (SLKT), leading some groups to minimize immunosuppressive (IS) regimens. However, the impact of preformed (pDSA) or de novo donor-specific antibodies (dnDSA) on the graft remains unclear. Methods We performed a retrospective analysis of 102 consecutive SLKT patients to study the impact of anti-HLA antibodies. Results Anti-HLA antibodies were detected in 75 recipients (class I 23.8%, both classes I and II 23.8%, and class II 14.3%). In total, 42.8% of the patients had pDSA and 21.7% developed dnDSA. Overall patient survival at 1–3 and 5 years, was respectively 88, 84, and 80%. Acute rejection occurred respectively in 3 (2.9%) liver and 6 kidney (5.9%) recipients. pDSA with titers over 10,000 mean fluorescence intensity (14.3%) was associated with lower patient survival (40 vs. 82%) but not with acute rejection. In a multivariable Cox regression analysis, the risk of death was associated with maleness, the highest titer of pDSA (p < 0.0007) or the sum of pDSA >10,000. Renal function did not differ between patients with class I pDSA (p = 0.631) and those with class II pDSA (p = 0.112) or between patients with and without a positive cross-match (p = 0.842). dnDSA were not associated with acute rejection, graft dysfunction or patient survival. IS minimization was not associated with rejection, graft dysfunction or death. Conclusion In SLKT, high levels of pDSA >10,000 were associated with lower patient survival, but not rejection or graft survival. Minimization of maintenance immunosuppression regimen was not associated with a poorer outcome.